Architecture, urbanism and history of the Jaraguá Neighborhood, Maceió/AL (Research, Society and Development, 2020)
Jaraguá is in one of the oldest neighborhoods in Maceió-AL. The history of the place mixes with that of the creation and the development of the capital itself. In order to contribute to the preservation of the history and architectural and cultural heritage of the Jaraguá neighborhood in Maceió/AL, this article selected three works considered emblematic. The three architectures selected were: Trapiche Jaraguá, Praça Dois Leões and the Museum of Image and Sound of Alagoas (MISA). Thus, we set out to study these buildings and how they reveal themselves in the face of a deterioration process that is present in the immediate vicinity. The methodology consisted of a bibliographic/documentary review, photographic records made in loco and technical visits. The research results in a more in-depth understanding of the neighborhood's history and the three works provided a historical analysis of each building, its relationship with the surroundings and its contribution to the urban development of the neighborhood. The three architectures resisted due to a number of factors: the neighborhood was zoned as a special preservation area by the master plan; because they were able to assume different uses and because such architecture constituted a relationship directly and indirectly with the community.